TEORI CARROT AND STICKS DALAM MENUNJANG PERKEMBANGAN COMPETITION COMPLIANCE PROGRAMME INDONESIA - Adinda Aisyah Chairunnisa; Parulian Paidi Aritonang (LPPM Universitas Ekasakti Padang, 2023)
In an effort to encourage business actors to create fair and ethical business competition, the Business Competition Supervisory Commission (“KPPU”) recently issued a new regulation regarding the Competition Compliance Program. The core of this program is expected to be a tool to ensure companies comply with Competition Laws, and to detect any violations of Competition Laws in business. The need to influence behavior and motivate individuals or business entities to comply with regulations related to business competition is in line with one of the objectives of the theory Carrot and Sticks. This theory is based on the assumption that rewards and punishments can be effective instruments to encourage compliance and prevent fraud.